Subversion and intertextuality in the Shrek saga - Mínguez López, Xavier (Didáctica. Lengua y Literatura, 2012)
The study of the cartoon seems to be increasingly important in determining the construction of literary competence of children and youth. In the present case, we see how the saga of the Shrek films contains a wealth of literary allusions, both related to folk sources, as with other current sources. The combination of references, along with the literary game that is offered, especially through intertextuality, makes Shrek an obligatory reference work.